Association of gastroesophageal reflux disease in children with bronchial asthma - Seemab Saleem; Saba Wamiq; Rabeea Saadat; Saima Manzoor (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVES: Gastroesophageal reflux disease (GERD) and asthma are often linked, with GERD potentially triggering or worsening asthma symptoms. This study aimed to determine the association between gastroesophageal reflux disease and bronchial asthma in children.METHODOLOGY: This case-control study was conducted at the Pediatric Medicine Department, Ibn-e-Siena Hospital, Multan, over a 6-month period. Children aged 3–12 years presenting to the pediatric outpatient department were consecutively enrolled. Cases were children diagnosed with bronchial asthma based on spirometry (FEV1/FVC <90% and FEV1 < 0% adjusted for age, gender, and height), while controls were children without respiratory symptoms and with normal spirometry. All participants underwent an upper gastrointestinal (GI) barium study, and gastroesophageal reflux disease (GERD) was diagnosed based on reflux esophagitis, hiatal hernia, or impaired gastric motility. Data were analyzed using SPSS version 23, and logistic regression was used to assess the association between GERD and asthma.RESULTS: The study included 63 cases and 63 controls, with a mean age of 7.01 ± 2.1 years and equal gender distribution. GERD prevalence was higher in cases (78.1% vs. 21.9%, p < 0.001). Asthmatic children had significantly lower BMI (16.0 ± 0.9 vs. 16.6 ± 0.9, p = 0.001). Logistic regression revealed GERD as an independent risk factor for asthma (OR: 4.9, 95% CI: 1.9–12.8, p=0.001), while higher BMI had a protective effect (OR: 0.55, 95% CI: 0.4–0.8, p=0.006)..Conclusion: GERD is significantly associated with bronchial asthma in children, while higher BMI appears protective. Managing GERD may play a role in asthma management.